Co-gasification of bituminous coal–pine sawdust blended char with H2O at temperatures of 750–850 °C. (15th September 2015) - Jeong, Hyo Jae; Hwang, In Sik; Hwang, Jungho
Highlights: Co-gasification of coal–biomass blended char with H2 O was conducted. Synergy on reactivity of coal–biomass blended char was observed. The activation energy and pre-exponential factor of the char gasification were obtained. The random pore model was determined to describe the char gasification the best. Abstract: This short communication reports on an experimental study that is an expansion of our previous study (Jeong et al., 2014). In the present study, the coal–biomass blended char was co-gasified with H2 O. Similar to the results of our previous study, the improvement of the blended char's reactivity with increasing the biomass amount was observed. The volume reaction model (VRM), shrinking core model (SCM), and random pore model (RPM) were applied to obtain the kinetic parameters, which were the pre-exponential factors and the activation energies. The RPM was determined to describe the char gasification the best according to the results of a comparison between the experimental reactivity and the results predicted using each model. Synergy of the reactivity was seen at all of the coal–biomass ratios and it increased as the amount of biomass increased.